1976
DOI: 10.1002/jez.1401960306
|View full text |Cite
|
Sign up to set email alerts
|

Role of gill Na+ + K+ ‐dependent ATPase in acclimation of blue crabs (Callinectes sapidus) to low salinity

Abstract: Male blue crabs (Callinectes sapidus Rathbun) were acclimated to salinities of 5 and 34 o/oo. Microsomal preparations of gills from these animals possessed Na+ + K+-dependent ATPase specific activities of 2.33 0.10 and 1.29 -+ 0.11 pmoles P i m i n per mg protein respectively, implicating the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
0
3

Year Published

1977
1977
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(44 citation statements)
references
References 21 publications
0
41
0
3
Order By: Relevance
“…Current knowledge on hypoosmotic acclimation in FW fish and crustaceans suggests that the predominant strategies employed in ion-poor conditions are to 1) increase ion uptake from the external medium and 2) reduce passive ion loss (31,47,68). Increased ion uptake is facilitated by increased expression and activity of ion transporters in the osmoregulatory tissues (17,18,26,32,48,59,60,71). In the euryhaline killifish Fundulus heteroclitus, increased Na ϩ -K ϩ -ATPase (NKA) activity and NKA ␣1a mRNA expression are observed in the gill following FW transfer (48).…”
mentioning
confidence: 99%
“…Current knowledge on hypoosmotic acclimation in FW fish and crustaceans suggests that the predominant strategies employed in ion-poor conditions are to 1) increase ion uptake from the external medium and 2) reduce passive ion loss (31,47,68). Increased ion uptake is facilitated by increased expression and activity of ion transporters in the osmoregulatory tissues (17,18,26,32,48,59,60,71). In the euryhaline killifish Fundulus heteroclitus, increased Na ϩ -K ϩ -ATPase (NKA) activity and NKA ␣1a mRNA expression are observed in the gill following FW transfer (48).…”
mentioning
confidence: 99%
“…During the molting process, a large net influx of water is crucial for increasing the animal's hydrostatic pressure in order to expand the body and break open the old exoskeleton. The acclimation of euryhaline crustaceans to dilute salinity is accompanied by decreased branchial water permeability [33], requiring increased Na/K-ATPase activity to establish an ion gradient for water influx to occur [19,34]. The significant increases observed in the Na/K-ATPase levels in the late premolt stage and postmolt stage in this study may indicate that Na/K-ATPase is involved in water uptake at molting.…”
Section: Discussionmentioning
confidence: 56%
“…69 The role of the NKA in regulating osmotic disturbances in crustaceans was first investigated using the blue crab, Callinectes sapidus acclimated to low salinities. 70 Further studies identified the gill as the most important site of osmotic regulation and discovered transporters and mechanisms that allowed some crustacean species to actively regulate extracellular osmolarity against steep osmotic gradients. 71,72 Although the existence of the NKA located in branchial epithelia of the cuttlefish Sepia officinalis was revealed using enzymatic assays in the late 70 ties, its role in branchial ion regulation was less well understood.…”
Section: The Ph Regulatory Machinerymentioning
confidence: 99%